Analysis of the impact of zakat fund distribution on mustahik productivity in Indonesia - Asya'bani, Nispia; Afifa, Ulfia Nur; Widiastuti, Tika; Mawardi, Imron; Soleh, Mochamad (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study examines the influence of zakat fund distribution on the productive behavior patterns of mustahiks in Indonesia, involving the moderating role of financial literacy. This study additionally examines the alterations in the behavior patterns of mustahiks following the receipt of zakat fund assistance.Methodology – This study employed a sequential explanatory mixed-methods design to examine the behavioral impacts of zakat distribution. In the quantitative phase, survey data were collected from 109 purposively selected mustahiks, using Likert-type items. The data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to estimate the effects of Zakat distribution on both productive and consumptive behavior, while also testing the moderating role of financial literacy.Findings – The results show that the variable of zakat fund distribution has a positive and significant effect on the productive and consumptive behavior of mustahik. The interplay of Sharia financial literacy as a moderating component can affect the connection between zakat fund distribution.Implications – The results of this research can be used as a reference for zakat institutions to monitor the impact of zakat fund distribution on beneficiaries and understand the factors influencing it.Originality – This research contributes to the existing literature by providing concrete evidence regarding the impact of zakat fund distribution on the behavior patterns of mustahiks, whether they receive productive or consumptive zakat. Additionally, there is an examination of the role of financial literacy, which acts as a factor that can strengthen or weaken that relationship.